EFEITO DOS METÓXI-CATECÓIS APOCININA, CURCUMINA E VANILINA SOBRE A ATIVIDADE CITOTÓXICA DO TAMOXIFENO - PEDROSO, LÍGIA SANTOS (2011)
Tamoxifen (TAM) is a synthetic nonsteroidal anti-estrogen, commonly prescribed to treat patients with breast cancer. Documented adverse effects of chronic TAM use include vaginal changes, menstrual irregularities, formation of endometrial polyps, ovarian cyst formation, thromboembolism, liver cancer, among others. Natural products are excellent candidates for new antitumor drugs, as they are widely-available and generally display low toxicity. Natural products may be more useful in combination with other chemotherapeutic drugs to obtain synergistic antitumor effects. The cytotoxic activity of curcumin has been shown in multiple tumor cell lines and has been widely studied. The vanillin has also shown activity on tumor cells due to their cytotoxic and cytostatic. Since the effects of apocynin are primarily due to its efficient inhibition of NADPH oxidase complex, and consequently, reactive oxygen species. It was studied the effect of treatment with the methoxy-catechols apocynin, curcumin and vanillin on tamoxifen (TAM)-induced cytotoxicity in normal and tumor cells. By assessing the release of hemoglobin and K+, the curcumin to be the only compound that decreased the cytotoxicity of TAM in red blood cells; however, in polymorphonuclear leukocytes, it was observed that apocynin, curcumin and vanillin all significantly increased the viability of cells exposed to TAM. Citotoxic activity was assessed in the human chronic myeloid leukemia (K562) cell line by (3-[4, 5-dimethylthiazol-2-yl]-2, 5- diphenyltetrazolium bromide, MTT) at 24, 48 and 72 h post-treatment. Among the methoxy-catechols (in association with TAM), vanillin presented the highest cytotoxic activity, followed by apocynin and curcumin. Measurement of antioxidant activity by the 2, 2’-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) radical cation decolorization assay revealed apocynin to have the highest activity, followed by curcumin and vanillin. No relationship was found between the antioxidant activities of the methoxy-catechols and the ability of these compounds to influence TAM-associated cytotoxicity. These results point to the potential therapeutic value of the tested methoxy-catechols in combination with TAM, particularly that of curcumin, which potentiates the cytotoxic effects of TAM on tumor cells (K562) and also decreases TAM-associated cytotoxicity in red blood cells.